Albumin is the major carrier protein for PFOS, PFOA, PFHxS, PFNA and PFDA in human plasma. (April 2020) - Forsthuber, Martin; Kaiser, Andreas Marius; Granitzer, Sebastian; Hassl, Ingrid; Hengstschläger, Markus; Stangl, Herbert; Gundacker, Claudia
Highlights: It is critical to know whether PFAS accumulate in the protein or the lipid fraction in human blood. Plasma and plasma fractions (albumin, >30 kDa, <30 kDa, lipoproteins) were analyzed for 11 PFAS. Albumin is the most important carrier of PFOS, PFOA, PFHxS, PFNA and PFDA in native human plasma. PFOS, PFOA, PFHxS, PFNA and PFDA have very little or no affinity for the lipoproteins VLDL, LDL, and HDL. Abstract: Perfluoroalkyl (PFAS) substances are widespread in the environment and in organisms. The fact that exposure to PFAS is associated with elevated cholesterol levels is a major concern for human health. Previous investigations, in which bovine serum albumin was frequently studied, indicate that PFOS, PFOA and PFNA bind to serum albumin. However, it is critical to know whether these and other PFAS have a preference for the protein or the lipid fraction in native human blood fractions. For this reason, blood samples from four young healthy volunteers (two women, two men, 23–31 years old) were used for protein size separation and fractionation by the Cohn method in combination with serial ultracentrifugation. The plasma fractions were analyzed for 11 PFAS using high-performance tandem mass spectrometry (HPLC-MS/MS). Although the data are based on a small sample, they clearly show that albumin is the most important carrier protein for PFOS, PFOA, PFHxS, PFNA and PFDA in native human plasma. These five compounds have very little or no affinity for lipoproteins. The confirmation of their transport through albumin is important for the epidemiology of PFAS. The present results must be verified by the examination of a larger number of persons.